Delegated safeguarding or surveillance by proxy?: education : the prevent statutory duty in action - Ghaemmaghami, Aram (International journal of law, crime and justice, 2023)
Research generated by Prevent is abundant. The majority of studies focus on the delivery of Prevent as a Countering Violent Extremism (CVE) initiative but rarely question the methodological pretences that underpin its practices. There is mounting pressure from the public sphere and sections of the research community that is casting doubt on Prevent's effectiveness as a policy as well as its potential to cause harm to the vulnerable communities it professes to serve through the pre-criminal space it occupies. This qualitative investigation evaluates the implementation of Prevent and its Statutory Duty at the community level, drawing on the experiences of Local Authority (LA) Prevent managers and their pastoral networks, which are predominantly populated by schools and education providers. It questions the validity of the Prevent manager's evidence base, using the Foucauldian concept of governmentality and the Bourdieusian conception of the educational field to navigate this dynamic.